Integrated (human health and animal health) surveillance and reporting system for 15 zoonotic diseases in Kenya - CGIAR Research Program on Agriculture for Nutrition and Health (2019)
System co-designed by ILRI researchers and piloted in three counties. Recent evaluation highlighted lack of integration between sectors, leading to disease under-reporting and inefficiencies. Operational research was conducted to refined the system. Results published and highlight importance of engaging with local stakeholders and providing timely feedback to ensure on-going compliance.